Role of Vascular Smooth Muscle Cell Phenotype Switching in Arteriogenesis - Jasni Viralippurath Ashraf (18518943) (2021)
Arteriogenesis is one of the primary physiological means by which the circulatory collateral system restores blood flow after significant arterial occlusion in peripheral arterial disease patients. Vascular smooth muscle cells (VSMCs) are the predominant cell type in collateral arteries and respond to altered blood flow and inflammatory conditions after an arterial occlusion by switching their phenotype between quiescent contractile and proliferative synthetic states. Maintaining the contractile state of VSMC is required for collateral vascular function to regulate blood vessel tone and blood flow during arteriogenesis, whereas synthetic SMCs are crucial in the growth and remodeling of the collateral media layer to establish more stable conduit arteries. Timely VSMC phenotype switching requires a set of coordinated actions of molecular and cellular mediators to result in an expansive remodeling of collaterals that restores the blood flow effectively into downstream ischemic tissues. This review overviews the role of VSMC phenotypic switching in the physiological arteriogenesis process and how the VSMC phenotype is affected by the primary triggers of arteriogenesis such as blood flow hemodynamic forces and inflammation. Better understanding the role of VSMC phenotype switching during arteriogenesis can identify novel therapeutic strategies to enhance revascularization in peripheral arterial disease. Other Information Published in: International Journal of Molecular Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ijms221910585